Knowledge or ignorance about correct use of inhalers among physicians in Primary Health Care Centers in Serbia - Marina Fišeković-Kremić (Биомедицинска истраживања, 2020)
Introduction: In daily use, a large majority of patients make inhalation errors. Primary health care doctors have an important role in preventing improper use of inhalers. The aim of this study is to evaluate the level of knowledge regarding the correct use of inhalers among physicians who work in primary health care centers as well as to evaluate the method of acquiring knowledge regarding an adequate inhalation technique. Methods: The research belonged to a cross sectional study, conducted on March 2019., in Belgrade, Serbia. The sample consisted of physicians who work in primary health care centers in Serbia. The data were collected by means of a questionnaire. The results were shown by parameters of descriptive statistics. The difference in the number of points among the two groups and other variables were tested by means of X2 test. The data were analyzed using SPSS 20. Results: The survey included 364 physicians in primary health care. 86.5% of them were female respondents. The mean work experience was 19 ± 11.22 years. In half of respondents family medicine was the scope of specialty (53%). The majority of respondents acquired knowledge about the correct use of inhalers by participating in lectures and workshops (50.3%). It was found that the physicians possessed an unsatisfactory level of knowledge. Conclusion: Primary health care physicians possess inadequate knowledge and skills concerning the proper use of inhalers. Lectures and workshops are not sufficient enough to educate doctors concerning the use of inhalers.
Keywords: inhalers; knowledge; education; general practice